Gambaran Keharmonisan Keluarga Di Tinjau Dari Peran Suami dan Isteri - Cindy Marisa; Evi Fitriyanti; Sri Utami (FKIP, Universitas Palangka Raya, 2021)
Many divorce cases are motivated by inharmonious family conditions, which occur due to not working the roles played by husband and wife. This study aims to reveal how the picture of the family in terms of the role of husband and wife in the Greater Jakarta area. This study involved 44 married couples who were selected by purposive sampling technique. The data in this study were conducted using a family harmony scale. The results in this study found that family harmony was in the Harmonious category, with a proportion of harmony of 68%, with the largest contribution to the aspect of affection by 26.43% and the aspect of kindness to God Almighty by 20.21%. Meanwhile, the lowest contribution was in the aspect of living facilities at 4.86%. This research can be a picture of a married couple to improve family harmony.